Blood Test. - Jones, W.D.
This paper describes how vascular patterns can provide a new means of identification and authentication. The new type of biometric identification device takes advantage of the fact that the network of vessels in each person's hand forms a pattern that can be distinguished from anyone else's. Unlike fingerprint scanners, vascular recognition systems do not require users to touch the sensors and remain unaffected by a user's blood pressure. With a strong combination of usability and accuracy, vascular recognition systems have the potential to be used in a wide range of applications
Keywords: Fujitsu; Hitachi; TechSphere; Authentication; Biometric identification device; Identification; Physical access control; Vascular pattern recognition; Vessels